2014
DOI: 10.1007/s11661-014-2596-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-metallic Inclusions on Machinability of Free-Cutting Steels Investigated by Nano-Indentation Measurements

Abstract: In the present paper, the nano-indentation technique is used to investigate the effects of inclusions on machinability of free-cutting steel. Firstly, the hardness, elastic moduli, and loaddisplacement curves of inclusions are analyzed and compared with matrix. Secondly, the effects of inclusions on machinability are investigated using nano-indentation measurements and thermodynamic calculations. Lastly, errors of nano-indentation measurements and macrohardness tests are analyzed. The hardness of BN is lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…However, it is also reported that some inclusions (such as MnS and Ca-modified oxides, among others) can help to improve the steel machinability (for instance by decreasing the wear on the cutting tool, thus extending the tool's life) [2]. Previous studies [3][4][5] show that inclusions improve machinability primarily by two ways: (1) as a source of stress concentration effects, favoring machinability by reducing the cutting force and increasing the chip breakability during machining, (2) as a lubricant (tool protection layer) in the contact zone of the cutting tool and material (reducing the abrasive and chemical wear of the tool), which is beneficial for the tool life. Thus, modification of NMIs and control of their characteristics in steels during steel manufacturing are very important to balance favorable machinability properties with the desired mechanical property for diverse types of steels.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also reported that some inclusions (such as MnS and Ca-modified oxides, among others) can help to improve the steel machinability (for instance by decreasing the wear on the cutting tool, thus extending the tool's life) [2]. Previous studies [3][4][5] show that inclusions improve machinability primarily by two ways: (1) as a source of stress concentration effects, favoring machinability by reducing the cutting force and increasing the chip breakability during machining, (2) as a lubricant (tool protection layer) in the contact zone of the cutting tool and material (reducing the abrasive and chemical wear of the tool), which is beneficial for the tool life. Thus, modification of NMIs and control of their characteristics in steels during steel manufacturing are very important to balance favorable machinability properties with the desired mechanical property for diverse types of steels.…”
Section: Introductionmentioning
confidence: 99%
“…However, even when using the same tools to machine steels with similar mechanical properties, steels having different non-metallic inclusions (NMIs) also can show different machinabilities. [2][3][4][5][6][7][8][9][10][11][12][13][14] The different hardnesses and thermal expansions of NMIs in steels will play different roles (negative or positive) during the machining of these steels. Rigid inclusions (such as Al 2 O 3 , TiCN) will scratch the tool surface and decrease the tool life dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, will lead to an increased tool life and cutting surface quality. [1][2][3][4][5][6][7][8][9] Thus, a modification of NMIs is beneficial to balance the preferred machinability and required mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The allowable impurity content of steel, the morphology of impurities and their influence on steel strength (mainly under variable loads) have been analyzed by numerous authors. Despite years of research and analyses, our knowledge of the impact of non-metallic inclusions on the properties of steel elements is still ambiguous and limited [5,[10][11][12]. The aim of this study was to determine the influences of large non-metallic inclusions on bending fatigue strength hardened and tempered performed on industrially manufactured high-grade, carbon structural steel of high purity.…”
Section: Introductionmentioning
confidence: 99%